Usia Resiko Tinggi dan Perdarahan Post Partum - Ani Media Harumi; Kasiati Kasiati (Jurnal Informasi Kesehatan Indonesia (JIKI), 2017)
Abstract: The purpose of this study is to analyze the relationship of age high risk with the incidence ofbleeding post partum in dr. M. Soewandhie Surabaya hospital. This research is analytic with an approachof a sectional cross. The study population was all post partum mothers in the Dr. M. Soewandhie Surabayahospital in January 2016 to March 2017, which amounts to an average of 1840respondents while theresearch sample number 182. Measuring collection sheet data obtained by systematic random sampling.The Study was conducted Chi-Square test obtained mean count X2 (0,00) is less than Ã¡ (0.05) thenH0 is rejected and H1 accepted it means that there is a relationship between the age of high risk withbleeding post partum. Conclusion, there is a relationship between the age of high risk with the incidenceof bleeding post partum in the Spaceof the Maternity room Dr. Moch. Soewandhie Surabayahospital.